Strategic Doing - Morrison, Edward; Hutcheson, Scott; Nilsen, Elizabeth; Fadden, Janyce; Franklin, Nancy (Ascent Audio, 2019)
Our companies, our communities, and our planet are facing unprecedented challenges-challenges that will not be solved by a small group of people from a single entity. Today's leaders need a set of tools specifically designed to harness the power of collaborative networks. Strategic Doing introduces you to the new disciplines of agile strategy and collaborative leadership. You'll learn how to design and guide complex collaborations by following a discipline of simple rules that you won't find anywhere else. - Unleash the power of true collaboration - Learn and master the ten skills of agile leadership - Apply individual skills to targeted situations - Introduces a new discipline of leadership strategy Filled with compelling case studies, Strategic Doing outlines a new discipline of leadership strategy specifically designed for open, loosely-connected networks.